2012
DOI: 10.3390/s120404187
|View full text |Cite
|
Sign up to set email alerts
|

Reducing False Negative Reads in RFID Data Streams Using an Adaptive Sliding-Window Approach

Abstract: Unreliability of the data streams generated by RFID readers is among the primary factors which limit the widespread adoption of the RFID technology. RFID data cleaning is, therefore, an essential task in the RFID middleware systems in order to reduce reading errors, and to allow these data streams to be used to make a correct interpretation and analysis of the physical world they are representing. In this paper we propose an adaptive sliding-window based approach called WSTD which is capable of efficiently cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Their results showed that SMURF techniques could adjust window size and outperformed all static window schemes. Massawe et al (2012) proposed a window sub-range transition detection (WSTD) adaptive sliding window approach, which used binomial sampling to calculate the appropriate window size [36]. Their results show that the WSTD scheme outperformed SMURF.…”
Section: False Positive Detectionmentioning
confidence: 99%
“…Their results showed that SMURF techniques could adjust window size and outperformed all static window schemes. Massawe et al (2012) proposed a window sub-range transition detection (WSTD) adaptive sliding window approach, which used binomial sampling to calculate the appropriate window size [36]. Their results show that the WSTD scheme outperformed SMURF.…”
Section: False Positive Detectionmentioning
confidence: 99%
“…In this section, simulation is used to analyse the performance of the proposed duplicate reading detection and removal approach. In the experiment, we used the same RFID data streams as in [9,10,14,17]. The data streams have been generated using Poisson distribution to illustrate the tag arrival in such granule time.…”
Section: Performance Analysismentioning
confidence: 99%
“…These duplicate readings will flood the network bandwidth and may have adverse effect in applications such as stock management [9]. To address this problem, a variety of Bloom Filter-based [9,10,12,16] and non-BF-based [14,17] approaches have been proposed in the literature. The latter approaches include those that used sliding window [14,17] and landmark window in filtering duplicate readings [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Massawe et al . [ 30 ] proposed an adaptive sliding window based approach called Window Sub-Range Transition Detection (WSTD), where a binomial sampling concept was used to calculate the appropriate window size and π-estimator to estimate the number of tags as proposed by SMURF. WSTD then used the comparison of the two window sub-range observations or estimated tag counts and some rules to detect when transition occurred within the window and then adjusted the window size appropriately.…”
Section: Literature Reviewmentioning
confidence: 99%